Bio-Medical Waste Management: Effect of Educational Intervention Among Health Care Workers in Bangalore City Hospitals - Md Mustafa Ahmed; Vikas Jaiswal; Pradeep C; Manasa RV (Medsci Publications, 2016)
Background: Infectious waste management has always remained a neglected public health problem in the developing countries, resulting in high burden of environmental pollution affecting general masses. This study was conducted to know the effect of intervention on health care personnel's regarding BMW management. Objectives: To assess the impact of educational intervention on the KAP of HCP's regarding BMW management. Methodology: An interventional study was conducted among health care Personnel's in Bangalore city hospitals for a period between (January - December 2013) sample size of 550 was initially screened, and 151 were selected for intervention by using a pre-tested structured questionnaire. Results: This study indicates that the statistical difference between pre-intervention and post-intervention tests (p<0.01) was highly significant. There was 43% increase in knowledge about BMW management. Conclusion: This study has determined that training programs on the subject of waste management in the health sector has a significant effect in increasing the information level of the healthcare personnel.